Design and development of craniofacial soft tissue imaging system - Majid, Zulkepli (Penerbit UTM, 2007)
A prototype craniofacial imaging system has been developed in the study. As 3D photogrammetry system for acquiring craniofacial spatial data, the developed system completely consisted of data acquisition system and data reduction system.